2016
DOI: 10.17576/mjas-2016-2004-10
|View full text |Cite
|
Sign up to set email alerts
|

ADSORPTION OF ANIONIC DYES FROM AQUEOUS SOLUTIONS BY CALCINED AND UNCALCINED Mg/Al LAYERED DOUBLE HYDROXIDE

Abstract: The uptake of Acid Blue 29 (AB29), Reactive Orange 16 (RO16) and Reactive Red 120 (RR120) from aqueous solutions by calcined (CLDH) and uncalcined Mg/Al layered double hydroxide (LDH) has been investigated. The adsorption process was conducted in a batch mode at 25 °C. Anionic dye removal was more efficient using the CLDH rather than LDH. The adsorption process by CLDH involved reconstruction and hydration of the calcined LDH and intercalation of AB29, RO16 and RR120. Physical characterization using X-Ray Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…The Energy Dispersive X-ray spectroscopy (EDS) analysis of the solids was performed to investigate the incorporation extent of lanthanum in the precipitation product and the method The morphology of the samples consists of platelets or flakes more or less compact, sometimes stacked as packing of lamellas. This morphology is quite similar to that of layered double hydroxides containing divalent and trivalent ions of hydrotalcite type [24,25]. For the Zn4La sample, the particles of quite uniform shapes and sizes are seen to be formed by stacking of numerous platelets with irregular perimeters, generating formations looking as rice grains of about 0.3-0.5 micrometers.…”
Section: Sem/eds Analysismentioning
confidence: 52%
“…The Energy Dispersive X-ray spectroscopy (EDS) analysis of the solids was performed to investigate the incorporation extent of lanthanum in the precipitation product and the method The morphology of the samples consists of platelets or flakes more or less compact, sometimes stacked as packing of lamellas. This morphology is quite similar to that of layered double hydroxides containing divalent and trivalent ions of hydrotalcite type [24,25]. For the Zn4La sample, the particles of quite uniform shapes and sizes are seen to be formed by stacking of numerous platelets with irregular perimeters, generating formations looking as rice grains of about 0.3-0.5 micrometers.…”
Section: Sem/eds Analysismentioning
confidence: 52%
“…Both calcined and non-calcined types of clays have been investigated for the removal of reactive dyes but the calcined clays are preferred over noncalcined clays due to their higher surface area and also they show better dye binding capacity [Aguiar et al, 2013;Asouhidou et al, 2012]. The clay-like materials investigated for the removal of reactive dyes include nano-hydroxyapatite [Kyzas et al, 2013], layered double hydroxides (LDH) [Sumari et al, 2016;Aguiar et al, 2013;Asouhidou et al, 2012], Mg(OH) 2 -modified-kaolin [Amin et al, 2015], and also the sea-water neutralized and calcined red mud [de Jesus et al, 2015;de Souza et al, 2013;Wang et al, 2009]. The laccase-modified fumed silica [Kalkan et al, 2014], nano-alumina [Nadafi et al, 2014], zinc and magnesium oxide nanoparticles [Khoshhesab et al, 2015;Venkatesha et al, 2012], kaolinite and smectite [Errais et al, 2012], Mg(OH) 2 -coated bentonite [Chinoune et al, 2016], silylated palygorskite [Xue et al, 2010], and synthetic talc [Rahman et al, 2013] also can be included in this list of clay-like materials.…”
Section: Types Of Ion-exchange Adsorbentsmentioning
confidence: 99%
“…Raw kaolinite, Fouchana clay, and synthetic talc showed quite meager reactive dye binding capacity [Errais et al, 2012, Rahman et al, 2013. On the other hand, laccase modified fumed silica [Kalkan et al, 2014], seawater-neutralized red mud calcined at 500 °C [de Jesus et al, 2015], and calcined Mg/Al LDH [Sumari et al, 2016] showed quite good dye binding capacity. Of the clays investigated, non-calcined Mg/Al LDH showed the highest reactive dye binding capacity for the removal of C.I.…”
Section: Reactive Dye Binding Capacity Of Clay-like Adsorbents and Dymentioning
confidence: 99%
“…The phosphate adsorption isotherms were evaluated for LDH, LDH-c, CAF, CAF-LDH and CAF-LDH-c. For this, 20 mg of the produced materials were added to 10 mL of solutions containing different phosphate ions concentrations (from 10 mg/L to 1,000 mg/L) [25,26]. The suspensions were stirred for 24 h in a thermostatic bath at 30 °C and closed system.…”
Section: Adsorption Isothermsmentioning
confidence: 99%